EKSPERIMEN TANAMAN BAYAM MERAH (AMARANTHUS TRICOLOR L.) DI LAHAN GAMBUT SEBAGAI RANCANGAN LKPD BERBASIS STEM MATERI PERTUMBUHAN DAN PERKEMBANGAN - Kaila Budiya; Suwondo; Imam Mahadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The availability of STEM-based Student Worksheets (LKPD) that present real experimental data for quantitative analysis remains limited in senior high school biology learning, particularly for the topic of Plant Growth and Development. This study aimed to: (1) analyze the effect of dolomite and poultry manure application on the growth of red spinach (Amaranthus tricolor L.) in peatland; and (2) analyze the validity of a STEM-based LKPD on Plant Growth and Development for Grade XII senior high school students developed based on experimental data. The experiment used a Factorial Completely Randomized Design (CRD) consisting of four dolomite doses (0, 24, 36, 48 g/polybag) and four poultry manure doses (0, 180, 270, 360 g/polybag), forming 16 treatment combinations with three replications. Growth parameters measured included plant height, leaf number, root length, fresh weight, and dry weight. Data were analyzed using Analysis of Variance (ANOVA) and Duncan's Multiple Range Test (DMRT) at 5% significance level. The LKPD was developed using the ADDIE model with a STEM approach integrated into Discovery Learning, and validated using a Likert scale (1–4) by two expert lecturers and one biology teacher. Results showed that the combination of dolomite and poultry manure significantly affected all growth parameters. The best treatment, D3P3 (48 g dolomite + 360 g poultry manure per polybag), produced the highest plant height of 24.00 cm, an increase of 674.19% compared to the control (3.10 cm), with leaf number 7.67, root length 6.57 cm, fresh weight 7.80 g, dry weight 2.22 g, and soil pH 6.07. The STEM-based LKPD obtained an overall validation score of 3.63 (Very Valid) and is suitable for use as a contextual learning material in Grade XII senior high school biology.